Délvidék megszállása és a déli demarkációs vonal kialakulása = The occupation of the Southland and the formation of the South demarcation line - Suba, János (Közép-Európai Közlemények, 2018)
Croatia left the Monarchy on 29th October, 1918. The Balkan troops of the Entente reached the line of the Sava-Danube at the end of October. The Serbian troops stepped on the territory of South-Bánát on 7th November, after they had followed the German army pulling back and had avoided any armed clashes. Three Serbian divisions carried out the execution of the Belgrade Cease Fire Agreement, i.e. the Croatia of the territories in the South of the demarcation line. One division already occupied the area to the line of Antalfa-Temesvár on 12th November, another did so to the line of Baja–Szabadka until 13th November, while the third crossed the River Drava and occupied the area of the Baranya bridgehead to the line of Siklós-Villány. Then they invaded Pécs and Mohács on 14th November. As a result, the towns near the demarcation line were occupied earlier by the Serbian troops than those in the territories behind them. This study reviews the occupation of the Southland, and the diplomatic fights that were taking place at the same time.